2023
DOI: 10.3390/foods12101944
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Trend in Microbial Changes during the Fermentation of Black Tea and Its Effect on the Quality

Abstract: The role of tea endophytes in black tea fermentation and their impact on black tea quality remain unclear. We collected fresh leaves of Bixiangzao and Mingfeng tea and processed them into black tea, while testing the biochemical composition of both the fresh leaves and the black tea. We also used high-throughput techniques, such as 16S rRNA, to analyze the dynamic changes in the microbial community structure and function during black tea processing in order to investigate the influence of dominant microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The image information of the samples was collected every hour, and at the same time, the samples were processed as frozen samples, which were used to analyze the subsequent physicochemical compositions. Figure 2b,c show the process of variation of the content of the thearubigin and catechin fractions in the samples with the fermentation time of black tea, which generally showed a gradual decrease in the change, mainly because during the fermentation process, polyphenols dominated by catechins underwent enzymatic oxidation to form theaflavin and thearubigin, which were then further polymerized into theabrownine as the fermentation process proceeded [21]. Figure 2d shows the correlation analysis graph between the content of catechin fractions and thearubigin content, and the results showed that the catechin content and thearubigin fractions showed a significant positive correlation with the fermentation time (p < 0.05).…”
Section: Results Of Physicochemical and Correlation Analysis Of Samplesmentioning
confidence: 99%
“…The image information of the samples was collected every hour, and at the same time, the samples were processed as frozen samples, which were used to analyze the subsequent physicochemical compositions. Figure 2b,c show the process of variation of the content of the thearubigin and catechin fractions in the samples with the fermentation time of black tea, which generally showed a gradual decrease in the change, mainly because during the fermentation process, polyphenols dominated by catechins underwent enzymatic oxidation to form theaflavin and thearubigin, which were then further polymerized into theabrownine as the fermentation process proceeded [21]. Figure 2d shows the correlation analysis graph between the content of catechin fractions and thearubigin content, and the results showed that the catechin content and thearubigin fractions showed a significant positive correlation with the fermentation time (p < 0.05).…”
Section: Results Of Physicochemical and Correlation Analysis Of Samplesmentioning
confidence: 99%